Implementación de un sistema web para un repositorio de actas y resoluciones, aplicando técnicas de “Data Management” para la “Asociación de Empleados de la UTC - Chicaiza Vela, Wilson Leonardo (2022)
The technological proposal was made in the Employees Association from Cotopaxi Technical University, whose main aim is to "Implement a records and resolutions repository web system for public information access and search”, which it was applied the adaptation of agile practices methodologies in the project development management process, in other words, it was used certain Scrum artifacts, together with UML unified language notations to better understand the system functionality and logic, while it was used data management and security techniques (Data Management) in the process of developing the system’s coding with the Python programming language and the Django framework, the same way, it was implement optical character recognition (OCR), also for a document specialized search based on its internal content and the performance of visual indicators both the views total number per file and the files total number uploaded to the system, thus, getting a system that it can be managed documents, so that the visitors or members of same association can have access to the public information, thus, complying with a constitutional decree. On the other hand, it has been developed the user manual, which it can help the president from association to learn more about the system correct use